2006
DOI: 10.1007/s10886-006-9124-x
|View full text |Cite
|
Sign up to set email alerts
|

From Terpenoids to Aliphatic Acids: Further Evidence for Late-Instar Switch in Osmeterial Defense as a Characteristic Trait of Swallowtail Butterflies in the Tribe Papilionini

Abstract: We compared the chemical compositions of the osmeterial secretions of fourth and fifth (last) instars of eight swallowtail species of the tribe Papilionini. Four species (Papilio demoleus, P. polytes, P. paris, and P. macilentus) are Asian Rutaceae-feeding swallowtails. The other four (Chilasa epicydes, C. agestor, P. troilus, and P. glaucus) represent more distant clades within the Papilionini and species with larval hosts in other plant families. We conducted a quantitative analysis for six species, but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…It is most likely that volatile terpenes accumulated in the secretory cavities are involved in defense against insect damage. On the other hand, it is well known that volatile terpenesproducing Citrus plants including Japanese pepper are hosts for the larvae of a swallowtail butterflies (Honda and Hayashi 1995;Ômura et al 2006). When the chemical composition in the osmeterial secretions from larvae of some swallowtail species of the tribe Papilionini was analyzed, volatile terpenes including D-limonene, β-phellandrene, and β-caryophyllene were detected, suggesting that ZpTPSs might contribute to ecological interaction between a swallowtail and Japanese pepper via volatile terpenes.…”
Section: Localization Of Volatile Compoundsmentioning
confidence: 99%
“…It is most likely that volatile terpenes accumulated in the secretory cavities are involved in defense against insect damage. On the other hand, it is well known that volatile terpenesproducing Citrus plants including Japanese pepper are hosts for the larvae of a swallowtail butterflies (Honda and Hayashi 1995;Ômura et al 2006). When the chemical composition in the osmeterial secretions from larvae of some swallowtail species of the tribe Papilionini was analyzed, volatile terpenes including D-limonene, β-phellandrene, and β-caryophyllene were detected, suggesting that ZpTPSs might contribute to ecological interaction between a swallowtail and Japanese pepper via volatile terpenes.…”
Section: Localization Of Volatile Compoundsmentioning
confidence: 99%
“…In contrast, examination of lycaenid and papilionid larvae showed no evidence of prosternal glands. However, papilionid larvae are well documented to possess an analogous bifurcate eversible dorsal gland just behind the head, which secretes defensive chemicals (Eisner & Meinwald 1965;Omura et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…samples as well as in N. menapia and P. sonora, and likely have a defensive function. Terpenoids dominate the osmeterial secretions of early-mid instar papilionid larvae whose major enemies are invertebrate predators (Omura et al 2006), and also were found in prosternal glands of nymphalid larvae, Dione juno and Abanote hylonome (Osborn & Jaffe 1998). All Argynnis spp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of deterrent and toxic compounds is reported in the osmeterial secretions of several Troidini (Honda, 1980(Honda, , 1983Omura et al, 2006). The presence of AAs in this organ is also widespread in the tribe Troidini; nevertheless, their ecological role is not well established (Nishida, 1995;Sime et al, 2000).…”
Section: Discussionmentioning
confidence: 99%